2022
DOI: 10.3390/agriculture12020147
|View full text |Cite
|
Sign up to set email alerts
|

The Agro-Climatic Change Characteristics across China during the Latest Decades

Abstract: Climate change has been highlighted over the last decades worldwide, with pronounced higher warming trends for China. Induced by climate change, to some extent, agricultural production has changed, as well as the climatic resources during the agricultural growing season. An obvious longer potential agricultural growing season (PAGS) was detected in the latest decades from 1961–2020. The spatial–temporal characteristics of change and variation of climatic resources during the PAGS were explored, utilizing compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Even then, research results from MK test analysis of heat exposure via the investigated phenological phase still suggested that rice plants were increasingly being exposed to extreme heat with rising global mean temperatures since the 2000s, particularly with obvious increased trends in regional exposure since 2010. Moreover, such a trend would be more severe with future warming, which was consistent with the findings of previous studies [9,14,68]. In the near future, we could conduct field experiments under relevant critical temperatures at different phenological stages to verify the reliability of a critical threshold database or improve the precision of the threshold to decimal places at the region scale.…”
Section: Uncertainties and Limitationssupporting
confidence: 87%
“…Even then, research results from MK test analysis of heat exposure via the investigated phenological phase still suggested that rice plants were increasingly being exposed to extreme heat with rising global mean temperatures since the 2000s, particularly with obvious increased trends in regional exposure since 2010. Moreover, such a trend would be more severe with future warming, which was consistent with the findings of previous studies [9,14,68]. In the near future, we could conduct field experiments under relevant critical temperatures at different phenological stages to verify the reliability of a critical threshold database or improve the precision of the threshold to decimal places at the region scale.…”
Section: Uncertainties and Limitationssupporting
confidence: 87%